# Volgorde van bewerkingen (gevorderd)

#### Reken uit

1. $$11+6.(-20)$$
2. $$(-8).(-10)+13$$
3. $$3+7.6^2-4$$
4. $$2.(-2)-7.(-4)-7$$
5. $$9-\sqrt{313-4.6^2}$$
6. $$\left(-\dfrac{6}{5}\cdot\dfrac{35}{54}-\dfrac{1}{9}\right)^2$$
7. $$\left(-\dfrac{5}{3}\cdot\dfrac{33}{65}-\dfrac{1}{13}\right)^2$$
8. $$8+3.(2^2-11)$$
9. $$-6.\sqrt{\frac{169}{49}}-\left[(\frac{-9}{7}-9)-(-3)^3\right]$$
10. $$4+10.2-66:6+7$$
11. $$(-13).(-5)+7$$
12. $$4+4.(5^2-7)$$

#### Reken uit

##### Verbetersleutel

1. $$11+6.(-20)=11+(-120)=-109$$
2. $$(-8).(-10)+13=80+13=93$$
3. $$3+7.6^2-4=3+7.36-4=3+252-4=251$$
4. $$2.(-2)-7.(-4)-7=-4+28-7=17$$
5. $$9-\sqrt{313-4.6^2}=9-\sqrt{313-4.36}=9-\sqrt{313-144}=9-\sqrt{169}=9-13=-4$$
6. $$\left(-\dfrac{6}{5}\cdot\dfrac{35}{54}-\dfrac{1}{9}\right)^2= \left(-\dfrac{6.35}{5.54}-\dfrac{1}{9}\right)^2= \left(-\dfrac{7}{9}-\dfrac{1}{9}\right)^2= \left(-\dfrac{7}{9}-\dfrac{1}{9}\right)^2= \left(\dfrac{-8}{9}\right)^2= \dfrac{64}{81}$$
7. $$\left(-\dfrac{5}{3}\cdot\dfrac{33}{65}-\dfrac{1}{13}\right)^2= \left(-\dfrac{5.33}{3.65}-\dfrac{1}{13}\right)^2= \left(-\dfrac{11}{13}-\dfrac{1}{13}\right)^2= \left(-\dfrac{11}{13}-\dfrac{1}{13}\right)^2= \left(\dfrac{-12}{13}\right)^2= \dfrac{144}{169}$$
8. $$8+3.(2^2-11)=8+3.(4-11)=8+3.(-7)=8+-21=-13$$
9. $$-6.\sqrt{\frac{169}{49}}-\left[(\frac{-9}{7}-9)-(-3)^3\right]=-6.\frac{13}{7}-\left[(\frac{-9}{7}-9)+27\right]=\frac{-78}{7}-\left[(\frac{-72}{7})+27\right]=\frac{-78}{7}-\left[\frac{117}{7}\right]=\frac{-195}{7}$$
10. $$4+10.2-66:6+7=4+20-11+7=20$$
11. $$(-13).(-5)+7=65+7=72$$
12. $$4+4.(5^2-7)=4+4.(25-7)=4+4.(18)=4+72=76$$
Oefeningengenerator vanhoeckes.be/wiskunde 2023-06-07 17:49:59